2019
DOI: 10.24075/brsmu.2019.051
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of image visualization simulator technology for physical rehabilitation of children with cerebral palsy through play

Abstract: The number of children born with cerebral palsy (CP) remains stably high. Novel approaches for rehabilitation of such patients are being sought. This study aimed to define the efficiency of the image visualization technologies in play activity for the physical rehabilitation of children with cerebral palsy. Sixteen boys with spastic diplegia aged 7–9 participated in the study. They were divided into treatment group (TG) and control group (CG), 8 children each. The TG patients were trained using the virtual rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Our search identified nine longitudinal studies as reported in Table 1 (34)(35)(36)(37)(38)(39)(40)(41)(42). According to the PEDro scores, one of the most interesting paper was the one by Choi et al (35), showing that children with chronic brain injury (including CP), treated by virtual reality and occupational therapy, significantly improved upper-limb dexterity functions, performance of daily activities, and forearm supination, as compared to the control group.…”
Section: Gaming Technologies In Longitudinal Neurorehabilitation Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search identified nine longitudinal studies as reported in Table 1 (34)(35)(36)(37)(38)(39)(40)(41)(42). According to the PEDro scores, one of the most interesting paper was the one by Choi et al (35), showing that children with chronic brain injury (including CP), treated by virtual reality and occupational therapy, significantly improved upper-limb dexterity functions, performance of daily activities, and forearm supination, as compared to the control group.…”
Section: Gaming Technologies In Longitudinal Neurorehabilitation Trialsmentioning
confidence: 99%
“…Wider improvements were observed for children with more severe motor impairment. Gorelik et al (38) showed that the Krisaf training simulator-based rehabilitation led to significant refinement of motor capabilities in children with spastic CP. Also, Tarakci et al (39) reported a significant balance improvement in children and adolescents with CP treated by using Nintendo-Wii-Fit balance board.…”
Section: Gaming Technologies In Longitudinal Neurorehabilitation Trialsmentioning
confidence: 99%
“…The disease represents the synthesis of the cognitive, sensory, motor and behavioral developmental deficits of a child and would find in the metaverse an opportunity to carry out a true multidimensional rehabilitation, thanks to a well-tested and customized rehabilitation protocol. Many studies have already reported positive results of clinical trials based on digital gaming technologies [ 47 ] and virtual reality [ 48 , 49 ] in children with cerebral palsy, as well as studies with the therapist not in person [ 50 ]. However, a recent systematic review found that the effect of VR in the rehabilitation of the upper limb of children with CP remains unclear [ 51 ].…”
Section: The Basis For Applying Metaverse-related Technology In Neuro...mentioning
confidence: 99%